1996
DOI: 10.1038/ki.1996.427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water diuresis and water restriction on expression of HSPs-27, -60 and -70 in rat kidney

Abstract: Expression of HSP-27, HSP-60 and HSP-70 was estimated in the cortex, outer medulla and inner medulla (papilla) of rats undergoing water diuresis or water restriction for two days. The mRNAs for HSP-27 and HSP-60 in renal papilla were two- to threefold greater in rats during water restriction than in those excreting a dilute urine, but levels of mRNA for HSP-70 were not reduced by water diuresis and Western analysis for HSP-70 protein showed no difference between water-loaded and water-restricted animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…For HSP25, one study of human breast cancer cells (MCF-7) has reported that HSP25 protein can be enhanced by hyperosmolality [16]. Consistent with this finding is the in vivo observation that transcription of HSP25 mRNA in the renal papilla is enhanced [27] during short-term water restriction. However, no data are available for the change of HSP25 protein content under these in vivo conditions.…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations
“…For HSP25, one study of human breast cancer cells (MCF-7) has reported that HSP25 protein can be enhanced by hyperosmolality [16]. Consistent with this finding is the in vivo observation that transcription of HSP25 mRNA in the renal papilla is enhanced [27] during short-term water restriction. However, no data are available for the change of HSP25 protein content under these in vivo conditions.…”
Section: Introductionsupporting
confidence: 50%
“…In our investigations HSP60 was unaffected by the different experimental protocols. Medina et al [27] have observed a slight increase of HSP60 mRNA in rats after 2 days of water restriction. This suggests that HSP60 may participate in the early response to acute osmolar changes, possibly by supporting the enhanced energy supply of medullary cells during adaptive processes.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This distribution pattern, however, is not observed for other members of the HSP family, such as the constitutively expressed HSP73 (also termed HSC70) and HSP60 [11,13]. In addition, the expression of HSP25 mRNA [14], HSP72 [8,13], and OSP94 mRNA [10] changes appropriately with the diuretic state.…”
mentioning
confidence: 99%